Aquaculture Status in Southern Bangladesh With Special Emphasis on Disease Induced Loss (Dhaka University Journal of Biological Sciences, 2023)
Culture fisheries contributes a major share of fisheries production of Bangladesh which is the accumulation of aquaculture production of every fish farms of the country. However, the actual production of cultured fish (finfish and shellfish) and cost-benefit of the farms are not well documented. Moreover, the farms must overcome a lot of constrains for sustainable production. The present study was thus designed to determine the present aquaculture status in some parts of Bangladesh and to identify the problems for the loss of aquaculture production through questionnaire survey between July 2019 and January 2020. The study areas included Bhola, Rangamati, Khulna, Satkhira, Jashore and Madaripur upazila. In the study area, the relationship between different aspects of aquaculture was determined where pond size and production cost per hectare; pond size and profit per hectare and per unit production cost and profit were found to be significantly and positively correlated. The production and production cost per hectare were also determined which were 3.52±0.40 metric tons and 6260±987 USD, respectively. The fish farmers reported some degrees of reduction of profits compare to the profit obtained during 2018-2019. The reduction of expected profit in different regions ranged between 10 and 33%. The major causes of the production loss in the survey regions were related to disease, seed and feed. Among different diseases viral, bacterial and parasitic diseases were reported where diseases were identified based on the symptoms. Findings of the present study suggest that incorporation of management, modern technology and economic aspects for steady growth of aquaculture sector is needed in Bangladesh.Dhaka Univ. J. Biol. Sci. 31(2): 257-271, 2022 (July)